Strengthening Legal Protection for Indonesian Fisheries Exports in International Trade - La Ilman; M. Umar Kelibia; Ide Raunas; Harmoko Harmoko; Raden Giri; Annie Myranika (International Journal of Business and Quality Research, 2026)
This study examines the importance of strengthening legal protection for Indonesian fisheries exports within the framework of international trade. As one of the world’s largest producers of marine resources, Indonesia holds significant potential in the global fisheries market. However, the competitiveness of its fisheries exports is often constrained by complex international regulations, including sanitary and phytosanitary standards, traceability requirements, and sustainability certifications imposed by importing countries. These regulatory challenges highlight the critical role of international trade law in shaping market access and export performance. This research adopts a normative juridical approach, analyzing international legal instruments, trade agreements, and national regulatory frameworks relevant to fisheries exports. The findings reveal that while existing legal frameworks provide opportunities for market expansion, gaps in regulatory alignment, enforcement mechanisms, and institutional capacity limit their effectiveness. Additionally, issues such as illegal, unreported, and unregulated (IUU) fishing, as well as environmental compliance, pose significant legal risks for Indonesian exporters. The study emphasizes the need for harmonization between domestic regulations and international standards, as well as the strengthening of institutional governance and compliance mechanisms. Enhancing legal protection is essential to ensure sustainable fisheries practices, improve export competitiveness, and secure Indonesia’s position in the global seafood market. Keywords: International Trade Law; Fisheries Exports; Legal Protection; Indonesia; Sanitary and Phytosanitary Measures